Evaluasi Sistem Pembelajaran (Menelaah Landasan Filosofis Evaluasi Pembelajaran dalam Perspektif Pengembangan Keilmuan di STAIN Kudus) - Mas'udi, Mas'udi (PIAUD Universitas Islam Negeri Sunan Kudus, 2014)
In the process of development, learning system applied at STAINKudus is fully geared to the transformation towards the archetypes that havebeen constituted. In the constitution of science that will be developed, theIslamic perspective on Transformative is the bedrock of scientific developmentwhich is formulated.Based on some of the policies that have been formulated by the government,the process of defining the curriculum in an institution is required to have itsapplication into the system that has been set. In this case, the application ofcurriculum system applied by STAIN Kudus have it’s completely to the provisionsof the governance system that has been set.From the formulation of this research can be revealed that the philosophicalfoundation of evaluation developed at STAIN Kudus designed completely relyupon the Principal Scientific Pattern set. Transformation effort from text tocontext, the individual to the social, from the theoretical to the practical areabecame the basis locomotive for STAIN Kudus curriculum development